Re-Evaluating Key Drivers Of Continuance Intention In Mobile Food Ordering Apps After Covid-19 Pandemic In Indonesia - Abas, Novel Idris; Puspawati , Dewita; Praswati , Aflit Nuryulia; Imaduddin , Helmi (Jurnal Economic Resource, 2025)
This study investigates why Indonesian Gen Y and Z users continue using specific mobile food ordering applications (MFOAs) post-pandemic, leading to market dominance by a few platforms. Analyzing 234 users, the research found that while saving time, money, and convenience all contribute to user satisfaction, only time and money savings directly influence the intention to continue using an app. Surprisingly, and contrary to previous literature, convenience does not directly impact user retention. These findings provide new insights for developers on improving long-term engagement by focusing on tangible benefits beyond mere convenience for these generations.